The Utilization of Interactive Video in English for Tourism Business Class - Darmayanti, Putu Sri; Kuntariati, Utik (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The usage of education technology into vocational school programs, can help vocational schools stay current with industry trends and provide students with the skills and knowledge needed for success in their chosen careers. However, the effective language instruction in vocational schools not only enhances students' linguistic abilities but also contributes to their overall employability and success in their chosen careers. The educators also known how to deliver the topic effectively by choosing an appropriate education technology due to the different educational background of the students. The educators must approach the unique needs of vocational students to make significant impact on their language proficiency and professional readiness. In this case, the researcher investigated interactive video as one of the media used by the lecturers. The investigation implemented qualitative method to gain the data. The result showed that the quality of the interactive video was good and all respondents prefer to utilize the interactive video rather than traditional video.